2019
DOI: 10.25056/jcm.2019.3.1.33
|View full text |Cite
|
Sign up to set email alerts
|

A functional movement screening of college students performing Pilates exercise

Abstract: Background: With the emergence of functional movement in the study of athleticism, Pilates exercise based on the activation of the body core is attracting much attention. Objective: This study aimed to investigate the changes in functional movement after performing Pilates exercise. Methods: A total of 31 college students at university K in seoul were included in this study. These students performed a 90-minute Pilates exercise twice a week for 16 weeks. Frequency analysis and paired t-test were performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…FMS ve pilates ilişkisine baktığımızda yapılan çalışmalarda; Pilates yaptıktan sonra iyileşmelerin gerçekleştiği ortaya koyulmuştur. Bunun sebebi olarak, pilates'in denge, stabilite ve hareketlilik gerektiren dinamik hareketleri bir araya getirmesinden kaynaklandığı görülmüş (Lim ve Park, 2019) ve pilates egzersizi fonksiyonel hareketi iyileştirmede üstün kabul edilmiştir (Yeon, 2019) (Roh, 2019).…”
Section: Tartışma Ve Sonuçunclassified
See 1 more Smart Citation
“…FMS ve pilates ilişkisine baktığımızda yapılan çalışmalarda; Pilates yaptıktan sonra iyileşmelerin gerçekleştiği ortaya koyulmuştur. Bunun sebebi olarak, pilates'in denge, stabilite ve hareketlilik gerektiren dinamik hareketleri bir araya getirmesinden kaynaklandığı görülmüş (Lim ve Park, 2019) ve pilates egzersizi fonksiyonel hareketi iyileştirmede üstün kabul edilmiştir (Yeon, 2019) (Roh, 2019).…”
Section: Tartışma Ve Sonuçunclassified
“…Bu faktörlerden dolayı herhangi bir sorun ortaya çıktığında, hareketlilik ve stabilite arasındaki denge değişir, dolayısıyla yaralanma riskini artırır. Bu nedenle, bahsedilen faktörleri ayırt etmek ve fonksiyonel hareket seviyesini belirlemek için pilates öncesi ve sonrası vücut koşullarını karşılaştırmak için fonksiyonel hareket analizi (FMS) test bataryası kullanılır (Roh, 2019).…”
Section: Introductionunclassified
“…Functional movement testing is a grading and ranking system to identify movement problems. Before proposing treatment and correction methods, they first confirm which conditions are acceptable and which are impossible for athletes (Roh, 2019). Coaches often decide whether an athlete is good or bad based on the athlete's strength, joint range of motion, and sports performance, but they never evaluate an athlete from the perspective of movement quality (Bonazza, et al, 2017).…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…For example, Shim et al found that aerobic exercise can improve functional movements and FMS scores in elderly women, but the sample sizes in the experimental group (n = 9) and the control group (n = 10) in this study were smaller [ 22 ]. Yeon et al concluded that Pilates can improve college students’ FMS scores and improve their functional movements, but the study adopted pre- and post-test design, lacking a control group [ 23 ]. In contrast, Wright et al found that 4 weeks of fundamental movement training could not improve FMS performance in children, which may be due to short-term interventions [ 24 ].…”
Section: Introductionmentioning
confidence: 99%